If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (w + -7)(w + 9) = 80 Reorder the terms: (-7 + w)(w + 9) = 80 Reorder the terms: (-7 + w)(9 + w) = 80 Multiply (-7 + w) * (9 + w) (-7(9 + w) + w(9 + w)) = 80 ((9 * -7 + w * -7) + w(9 + w)) = 80 ((-63 + -7w) + w(9 + w)) = 80 (-63 + -7w + (9 * w + w * w)) = 80 (-63 + -7w + (9w + w2)) = 80 Combine like terms: -7w + 9w = 2w (-63 + 2w + w2) = 80 Solving -63 + 2w + w2 = 80 Solving for variable 'w'. Reorder the terms: -63 + -80 + 2w + w2 = 80 + -80 Combine like terms: -63 + -80 = -143 -143 + 2w + w2 = 80 + -80 Combine like terms: 80 + -80 = 0 -143 + 2w + w2 = 0 Factor a trinomial. (-13 + -1w)(11 + -1w) = 0Subproblem 1
Set the factor '(-13 + -1w)' equal to zero and attempt to solve: Simplifying -13 + -1w = 0 Solving -13 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -1w = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -1w = 0 + 13 -1w = 0 + 13 Combine like terms: 0 + 13 = 13 -1w = 13 Divide each side by '-1'. w = -13 Simplifying w = -13Subproblem 2
Set the factor '(11 + -1w)' equal to zero and attempt to solve: Simplifying 11 + -1w = 0 Solving 11 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1w = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -1w = 0 + -11 -1w = 0 + -11 Combine like terms: 0 + -11 = -11 -1w = -11 Divide each side by '-1'. w = 11 Simplifying w = 11Solution
w = {-13, 11}
| 7(3z-8)=-21 | | 3/8x-8=64 | | 0.55x+4.95=x | | 2x^2+17x+15= | | -17-7m=13 | | -3+14s=14s-6-1 | | 10x+5x+15=180 | | -y+5=2x | | x+x+2+x+3=87 | | 14d-15=11d+d+11 | | 3x-3x+3=-3 | | 2+3f=20+2f | | 9-17y=20-11-17y | | -7x-27=8-x+19 | | 2x-3.6=12 | | 7x4/5 | | 3x+12x+5x=180 | | 4x-1.2=1-x | | 2/7(4m-18)1=12 | | 2x+12x*x-8x=x*x*x | | 3x-8y-4y+7x+2= | | g−7/3=7/2 | | 6x+4=4x+34 | | 4cosx=5sinx | | 6x/10-2x/10= | | -5-6b=10-6b | | 3(x-7)-5(2x+1)=x-26 | | f(x)=-2-3 | | -4n+5= | | 5+2b-9= | | -(2a+1)-(3a-5)= | | Y/2_16=4 |